PELAKSANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA SISWA TUNARUNGU DI SMALB NEGERI BATU - Miftahul Jannah; Anwar Sa’dullah; Lia Nur Atiqoh B.D (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The greatest impact of children with hearing impaired special needs is the occurrence of language poverty and in overall language acquisition. Therefore, special services are needed as well as special handling of expert educators. This journal describes how the implementation of PAI learning for deaf children in Batu State Senior High School. The study was conducted with the type of qualitative research in the form of field research or case studies. Data collection procedures are carried out using observation, interview and documentation methods. The results showed in the implementation of learning includes three stages, the first stage is making careful planning as outlined in the lesson plans, making lesson plans tailored to the conditions and characteristics of students. The second stage, namely the application of the lesson plan in the learning process by modifying it in its application, in the learning process the PAI teacher places more emphasis on direct application or practice using concrete or tangible objects. The third stage is assessment, assessment of deaf children in SMALB uses non-test testing techniques and emphasizes the affective and psychomotor aspects. Making questions by avoiding analytical problems.